2009
DOI: 10.1111/j.1600-0781.2009.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Acne‐photodynamic therapy with intra‐lesional injection of 5‐aminolevulinic acid

Abstract: Photodynamic therapy (PDT) is a treatment option for acne patients who fail to respond to conventional therapy. Although potent, we experience side effects such as erythema, exfoliation and dyspigmentation. In attempt to specify treatment and shorten the incubation time, we injected 5-aminolevulinic acid (ALA) to the individual lesion. The results of intralesional injection ILI-PDT and conventional PDT are compared in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 4 publications
(4 reference statements)
0
19
1
Order By: Relevance
“…Other topical photosensitizers, which have been studied less extensively, include indocyanine green (or methylene blue) and indole-3-acetic acid 32,33,108113. Indole-3-acetic acid in particular may have an important role in clinical practice, primarily because patients receiving indole-3-acetic acid for acne experience less pain.…”
Section: Pdt In Inflammatory Diseasesmentioning
confidence: 99%
“…Other topical photosensitizers, which have been studied less extensively, include indocyanine green (or methylene blue) and indole-3-acetic acid 32,33,108113. Indole-3-acetic acid in particular may have an important role in clinical practice, primarily because patients receiving indole-3-acetic acid for acne experience less pain.…”
Section: Pdt In Inflammatory Diseasesmentioning
confidence: 99%
“…32,33,[108][109][110][111][112][113] Indole-3-acetic acid in particular may have an important role in clinical practice, primarily because patients receiving indole-3-acetic acid for acne experience less pain. It also has promising practical aspects, requiring shorter incubation times whilst producing equivalent efficacy (Table 2).…”
Section: Other Photosensitizersmentioning
confidence: 99%
“…Moreover, a study showed that the fluorescence induced by the intralesional injection of the prodrug was present as early as 4 h [9] ; nonetheless, the time necessary to allow the conversion of the prodrug into the final photosensitizer is likely to be much shorter, as incubations ! 1 h were shown to be effective as well [2,8] . It has also been proposed that intralesional PDT may be particularly effective in inflammatory disorders in which the epidermal surface is intact or nearly intact and the dermis thickened for physiological (scalp) or pathological reasons (morphea) [10] .…”
mentioning
confidence: 99%
“…In black patients, intralesional PDT may overcome, if not the diminished penetration of light due to the increased melanin filter, at least the increased thickness of the stratum corneum [11] . Also according to our experience, this technique does not affect the compliance of patients [6] and causes fewer side effects (erythema, crusting) in the postirradiation period than conventional topical PDT [8] .…”
mentioning
confidence: 99%
See 1 more Smart Citation